Respostas
respondido por:
1
Olá!!!
A) x² - 6x + 5 = 0
a = 1
b = -6
c = 5
Delta: ∆ = b² - 4.a.c
∆ = (-6)² - 4.1.5
∆ = 36 - 20
∆ = 16
Raízes: X = -b ± √∆/2.a
X = -(-6) ± √16/2.1
X = 6 ± 4/2
X = 6 + 4/2 = 10/2 = 5
X = 6 - 4/2 = 2/2 = 1
S={ 5, 1 }
===============================
B) x² - 7x + 10 = 0
a = 1
b = -7
c = 10
∆ = (-7)² - 4.1.10
∆ = 49 - 40
∆ = 9
X = -(-7) ± √9/2.1
X = 7 ± 3/2
X = 7 + 3/2 = 10/2 = 5
X = 7 - 3/2 = 4/2 = 2
S={ 5, 2 }
★Espero ter ajudado!! tmj.
A) x² - 6x + 5 = 0
a = 1
b = -6
c = 5
Delta: ∆ = b² - 4.a.c
∆ = (-6)² - 4.1.5
∆ = 36 - 20
∆ = 16
Raízes: X = -b ± √∆/2.a
X = -(-6) ± √16/2.1
X = 6 ± 4/2
X = 6 + 4/2 = 10/2 = 5
X = 6 - 4/2 = 2/2 = 1
S={ 5, 1 }
===============================
B) x² - 7x + 10 = 0
a = 1
b = -7
c = 10
∆ = (-7)² - 4.1.10
∆ = 49 - 40
∆ = 9
X = -(-7) ± √9/2.1
X = 7 ± 3/2
X = 7 + 3/2 = 10/2 = 5
X = 7 - 3/2 = 4/2 = 2
S={ 5, 2 }
★Espero ter ajudado!! tmj.
Anônimo:
Obrigada!
respondido por:
0
A) x²-6x+5=0
Δ= (-6)² - 4 . 1 . 5
Δ= 36 - 20
Δ= 16
x= 6 ± 4 / 2
x'= 10 / 2 = 5
x"= 2 / 2 = 1
S={ 5 , 1 }
B) x²-7x+10=0
Δ= (-7)² - 4 . 1 . 10
Δ= 49 - 40
Δ= 9
x= 7 ± 3 / 2
x'= 10 / 2 = 5
x"= 4 / 2 = 2
S={ 5 , 2 }
Δ= (-6)² - 4 . 1 . 5
Δ= 36 - 20
Δ= 16
x= 6 ± 4 / 2
x'= 10 / 2 = 5
x"= 2 / 2 = 1
S={ 5 , 1 }
B) x²-7x+10=0
Δ= (-7)² - 4 . 1 . 10
Δ= 49 - 40
Δ= 9
x= 7 ± 3 / 2
x'= 10 / 2 = 5
x"= 4 / 2 = 2
S={ 5 , 2 }
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás